Plastic debris in rivers. (29th November 2019) - van Emmerik, Tim; Schwarz, Anna
Abstract: Plastic pollution in aquatic ecosystems is an emerging environmental risk, as it may negatively impacts ecology, endangers aquatic species, and causes economic damage. Rivers are known to play a crucial role in transporting land‐based plastic waste to the world's oceans, but riverine ecosystems are also directly affected by plastic pollution. To better quantify global plastic pollution transport and to effectively reduce sources and risks, a thorough understanding of origin, transport, fate, and effects of riverine plastic debris is crucial. In this overview paper, we discuss the current scientific state on plastic debris in rivers and evaluate existing knowledge gaps. We present a brief background of plastics, polymer types typically found in rivers, and the risk posed to aquatic ecosystems. Additionally, we elaborate on the origin and fate of riverine plastics, including processes and factors influencing plastic debris transport and its spatiotemporal variation. We present an overview of monitoring and modeling efforts to characterize riverine plastic transport, and give examples of typical values from around the world. Finally, we present an outlook to riverine plastic research. With this paper, we aim to present an inclusive and comprehensive overview of riverine plastic debris research to date and suggest multiple ways forward for future research. This article is categorized under: Science of Water > Water Quality Water and Life > Stresses and Pressures on Ecosystems Abstract :